Intraluminal Pulmonary Vein Stenosis in Children: A "New" Lesion. (July 2019) - Nasr, Viviane G.; Callahan, Ryan; Wichner, Zachary; Odegard, Kirsten C.; DiNardo, James A.
Abstract : Pulmonary vein stenosis (PVS) is a rare disorder that leads to progressive narrowing of the extrapulmonary veins. PVS has been reported in both children and adults and in its worse iteration leads to pulmonary hypertension, right ventricular failure, and death. Multiple etiologies of PVS have been described in children and adults. This review will focus on intraluminal PVS in children. Intraluminal PVS has an estimated incidence ranging from 0.0017% to 0.03%. It is associated with conditions such as prematurity, bronchopulmonary dysplasia, necrotizing enterocolitis, Smith-Lemli-Opitz syndrome, and Down syndrome. Cardiac catheterization and pulmonary vein angiography are the gold standard for diagnosis and anatomic delineation. Other imaging modalities including magnetic resonance imaging, chest tomography, and transesophageal echocardiography are increasingly being used. Mortality of PVS in children is approximately 50%. Predictors of mortality include involvement of ≥3 pulmonary veins, bilateral pulmonary vein involvement, onset of PVS in infancy, elevated pulmonary artery pressure or systolic pulmonary artery-to-aortic pressure ratio, right ventricular dysfunction, restenosis after surgery, distal/upstream disease, and disease progression to previously uninvolved pulmonary veins. Treatment includes catheter-based pulmonary vein dilations with or without stenting, surgical interventions, medical therapy, and in some instances, lung transplantation. Cardiac catheterization for PVS involves a comprehensive hemodynamic and anatomic assessment of the pulmonary veins as well as therapeutic transcatheter interventions. Several surgical strategies have been used. Sutureless repair is currently most commonly used, but patch venoplasty, endarterectomy, ostial resection, and reimplantation are used in select circumstances as well. Medical therapies such as imatinib mesylate and bevacizumab are increasingly being used in an effort to suppress the myofibroblastic proliferation seen in PVS patients. Lung transplantation has been used as an alternative treatment strategy for end-stage, refractory PVS. Nonetheless, despite the different innovative approaches used, morbidity and mortality remain high. At present, the preferred treatment strategy is frequent reassessment of disease progression to guide use of catheter-based and surgical interventions in conjunction with medical therapy.